Sestrin2 is a leucine sensor for the mTORC1 pathway - Wolfson, Rachel L.; Chantranupong, Lynne; Saxton, Robert A.; Shen, Kuang; Scaria, Sonia M.; Cantor, Jason R.; Sabatini, David M. (Science (American Association for the Advancement of Science), 2016)
Leucine is a proteogenic amino acid that also regulates many aspects of mammalian physiology, in large part by activating the mTOR complex 1 (mTORC1) protein kinase, a master growth controller. Amino acids signal to mTORC1 through the Rag guanosine triphosphatases (GTPases). Several factors regulate the Rags, including GATOR1, a GTPase-activating protein; GATOR2, a positive regulator of unknown function; and Sestrin2, a GATOR2-interacting protein that inhibits mTORC1 signaling. We find that leucine, but not arginine, disrupts the Sestrin2-GATOR2 interaction by binding to Sestrin2 with a dissociation constant of 20 micromolar, which is the leucine concentration that half-maximally activates mTORC1. The leucine-binding capacity of Sestrin2 is required for leucine to activate mTORC1 in cells. These results indicate that Sestrin2 is a leucine sensor for the mTORC1 pathway.